VIRAL HEPATITIS A TO E IN SOUTH MEDITERRANEAN COUNTRIES - Sanaa M. Kamal; Sara Mahmoud; Tamer Hafez; Runia EL Fouly (Mediterranean Journal of Hematology and Infectious Diseases)
Viral hepatitis represents an important health problem in the South Mediterranean countries, Egypt, Libya, Tunisia, Algeria and Morocco.  Emerging natural history and epidemiological information reveal differences in the overall epidemiology, risk factors and modes of transmission of viral hepatitis A, B, C, D, E infections in the South Mediterranean region. The differences in the in incidence and prevalence of viral hepatitis across North African countries is attributed to variations in health care  and sanitation standards, risk factors and immunization strategies. The active continuous population movement through travel, tourism and migration from and to the South Mediterranean countries contribute to the spread of infections due to hepatitis viruses across borders leading to outbreaks and emergence of new patterns of infection or introduction of uncommon genotypes in other countries, particularly in Europe.